Tourism activity among university students: a survey from universities in Łódź - Latosińska, Jolanta; Ludwicka, Dorota (Turyzm/Tourism, 2010)
The article presents conclusions on the tourism activity of university students in Łódź. It is based on a survey conducted in October and November 2008 among final year students at six state-run universities in Łódź. The article presents the socio-demographic structure of the respondents, their tourism trips and the factors influencing them, while the conclusions offer a functional model of recreation for the groups investigated.